2008
DOI: 10.1111/j.1365-2265.2008.03280.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of T4 replacement therapy on glucose metabolism in subjects with subclinical (SH) and overt hypothyroidism (OH)

Abstract: In summary, SH and OH are characterized by attenuated basal plasma insulin levels and increased glucose-induced insulin secretion. T4 replacement therapy partially ameliorates the insulin secretion profile and reduces the demand on pancreatic beta-cells after glucose challenge to an extent that exceeds any effect attributable to the improvement in insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
1
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 38 publications
12
67
1
11
Order By: Relevance
“…The severity of the disease is proportional to the severity of these disorders. The possible influence of subclinical forms of both hyperthyroidism and hypothyroidism on carbohydrate disorders is still under discussion [9,10,12].…”
Section: Insulin Resistance and Thyroid Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The severity of the disease is proportional to the severity of these disorders. The possible influence of subclinical forms of both hyperthyroidism and hypothyroidism on carbohydrate disorders is still under discussion [9,10,12].…”
Section: Insulin Resistance and Thyroid Diseasementioning
confidence: 99%
“…which, 20 minutes later, is followed by an i.v. administration of tolbutamide (dosage depends on body weight) that activates the secretion of endogenous insulin [2,10]. The test duration is three hours.…”
Section: Rycina 2 Wpływ Hormonów Tarczycy Na Metabolizm Glukozy U Pamentioning
confidence: 99%
“…Hypothyroidism is associated with deterioration of glucose metabolisms, and this effect is accompanied by reduced plasma insulin concentration (32). Several reports indicated that overt hypothyroidism is associated with profound changes in insulin sensitivity and insulin secretion, and these changes are reversible, at least in part, after recovery of thyroid function (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Последние данные свидетельствуют о том, что секреция инсулина при гипотиреозе снижена, так как после начала терапии левотироксином концентра-ции инсулина и проинсулина значительно увеличива-ются. И напротив, при гипотиреозе было выявлено по-вышение глюкозоиндуцированной секреции инсулина с последующим ее снижением на фоне терапии лево-тироксином, поскольку при восстановлении эутиреоза снижается нагрузка на бета-клетки [15].…”
Section: гипотиреоз и инсулинорезистентностьunclassified
“…Последние данные свидетельствуют о том, что секреция инсулина при гипотиреозе снижена, так как после начала терапии левотироксином концентра-ции инсулина и проинсулина значительно увеличива-ются. И напротив, при гипотиреозе было выявлено по-вышение глюкозоиндуцированной секреции инсулина с последующим ее снижением на фоне терапии лево-тироксином, поскольку при восстановлении эутиреоза снижается нагрузка на бета-клетки [15].При субклиническом гипотиреозе в нескольких работах проводилась оценка индекса НОМА; инсу-линорезистентность была выявлена в некоторых, но не во всех исследованиях. Тем не менее в иссле-дованиях, в которых инсулинорезистентности при субклиническом гипотиреозе выявлено не было, авторы обнаружили гиперинсулинемию как первый признак нарушения метаболизма глюкозы.…”
unclassified